Food nutrition impact toward rural consumer in Kelantan - Zul Ariff Abdul Latiff; Mohamad Amizi Ayob (2015)
Consumers‟ food consumption patterns are changing rapidly. Consumers are becoming more aware about the food they consume. They tend to consume food product which has food nutrition label so that they will get information from there. This study is focus on their awareness and intention about food nutrition labels when they purchase food product in Kelantan. A structured questionnaire was designed and used as an instrument to gather the information towards food nutrition labels among the consumers. A survey was conducted and distributed to 300 rural respondents in Kelantan, Malaysia. Descriptive statistics were used to analyze the data collected. The result indicate that most of the respondents aware of the food nutrition labels. The respondents also indicate that food labels not only about nutrition information but they believe food products which have labels is quality products.